Voltage Preconditioning Allows Modulated Gene Expression in Neurons Using PEI-complexed siRNA - Arati Sridharan; Chetan Patel; Jit Muthuswamy (Elsevier, 2013)
We present here a high efficiency, high viability siRNA-delivery method using a voltage-controlled chemical transfection strategy to achieve modulated delivery of polyethylenimine (PEI) complexed with siRNA in an in vitro culture of neuro2A cells and neurons. Low voltage pulses were applied to adherent cells before the administration of PEI-siRNA complexes. Live assays of neuro2a cells transfected with fluorescently tagged siRNA showed an increase in transfection efficiency from 62 ± 14% to 98 ± 3.8% (after −1 V). In primary hippocampal neurons, transfection efficiencies were increased from 30 ± 18% to 76 ± 18% (after −1 V). Negligible or low-level transfection was observed after preconditioning at higher voltages, suggesting an inverse relationship with applied voltage. Experiments with propidium iodide ruled out the role of electroporation in the transfection of siRNAs suggesting an alternate electro-endocytotic mechanism. In addition, image analysis of preconditioned and transfected cells demonstrates siRNA uptake and loading that is tuned to preconditioning voltage levels. There is approximately a fourfold increase in siRNA loading after preconditioning at −1 V compared with the same at ±2-3 V. Modulated gene expression is demonstrated in a functional knockdown of glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in neuro2A cells using siRNA. Cell density and dendritic morphological changes are also demonstrated in modulated knockdown of brain derived neurotrophic factor (BDNF) in primary hippocampal neurons. The method reported here has potential applications in the development of high-throughput screening systems for large libraries of siRNA molecules involving difficult-to-transfect cells like neurons.